PENYULUHAN PENANGANAN PASCAPANEN YANG BAIK BAGI PETANI PALA DI DESA LILIBOOI, KECAMATAN LEIHITU BARAT KABUPATEN MALUKU TENGAH, PROVINSI MALUKU - Grace Sipahelut, Sophia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2024)
Nutmeg is Indonesia's mainstay export commodity which brings in foreign exchange for this country. However, Indonesia's nutmeg productivity is still low and below the world average. For this reason, efforts are needed to improve the quality of Indonesian nutmeg, one of which is by increasing nutmeg farmers' knowledge about Good Handling Practices for nutmeg plants. This service activity aims to increase the knowledge, abilities and skills of nutmeg farmers in Lilibooi Village, West Leihitu District, Central Maluku Regency in handling harvest, post-harvest and nutmeg processing. This community service activity was attended by 15 nutmeg farmers. The methods used are counseling and evaluation. The material provided is related to how to harvest nutmeg, post-harvest handling of nutmeg seeds and mace, as well as packaging and storage of nutmeg seeds and mace. The evaluation results show that from this activity, nutmeg farmers gained additional knowledge and new technology related to the implementation of GHP for nutmeg crops.